Arterial and venous thrombosis in systemic and monogenic vasculitis - Bello, Federica; Fagni, Filippo; Bagni, Giacomo; Hill, Catherine L.; Mohammad, Aladdin J.; Moiseev, Sergey; Olivotto, Iacopo; Seyahi, Emire; Emmi, Giacomo (Nature Reviews Rheumatology, 2025)
Systemic vasculitis, common forms of which include anti-neutrophil cytoplasmic antibody-associated small-vessel vasculitis, large-vessel vasculitis and Behçet syndrome, are frequently complicated by arterial or venous thrombotic events (AVTEs). Newly identified entities such as DADA2 (deficiency of adenosine deaminase 2) and VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome, which are driven by genetic mutations, also exhibit vasculitic features and are associated with a high risk of AVTEs. AVTEs in systemic vasculitis, including monogenic forms of vasculitis, are due to the complex interaction of inflammation and coagulation. New insights into the pathogenetic mechanisms implicate endothelial dysfunction, immune complex deposition and the interplay of pro-inflammatory cytokines with prothrombotic factors, which collectively promote thrombus formation. AVTEs impose a substantial disease burden, complicate diagnosis and negatively affect prognosis by increasing the risk of morbidity and mortality. Early diagnosis and treatment are crucial to prevent lasting damage. Management strategies should target both thrombosis and underlying inflammation. Antithrombotic therapies, including low-dose aspirin, or oral anticoagulants should be used on the basis of individual thrombotic risk assessment. Immunosuppressive therapy is the cornerstone of treatment for arterial and venous thrombosis, particularly in Behçet syndrome, in which vascular inflammation has a crucial role in thrombotic complications.
CRIS-Team Scopus Importer:2025-05-16